Analisis Kemampuan Penalaran Matematis Siswa SMPN 4 Mataram Tahun Ajaran 2024/2025 Ditinjau Dari Gaya Belajar - Nayaningtyas, Carmelita Kusuma; Turmuzi , Muhammad; Wahyu Triutami, Tabita (Griya Journal of Mathematics Education and Application, 2025)
This study aims to describe the mathematical reasoning abilities of eighth-grade students at SMPN 4 Mataram based on their learning styles: visual, auditory, and kinesthetic. The reasoning indicators include making conjectures, representing ideas, performing mathematical manipulations, determining problem-solving strategies, drawing conclusions, and verifying the correctness of statements. This research uses a qualitative descriptive method. From 48 students who completed the learning style questionnaire, six students were selected as research subjects two from each learning style using purposive sampling. Data were collected through learning style questionnaires, mathematical reasoning tests, and interview guidelines. Data analysis was carried out through data reduction, data display, and drawing conclusions. The results showed that students with visual and auditory learning styles were able to meet all indicators of mathematical reasoning and were categorized as having high reasoning ability. In contrast, students with a kinesthetic learning style met only some indicators and were categorized as having moderate ability. These findings indicate that mathematical reasoning skills can differ based on students' learning styles.